PENGARUH BAURAN RITEL DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI SANYA SWALAYAN KOTA KENDARI - Dzulfikri Azis Muthalib (Journal Economics Technology And Entrepreneur, 2025)
This study aims to analyze the effect of retail mix and service quality on consumers’ purchase decisions at Sanya Swalayan in Kendari City. This research employs a quantitative approach with an explanatory research design. The research population consists of Sanya Swalayan customers, with a sample of 90 respondents determined based on the number of research indicators. A purposive sampling technique was applied. Data were collected through questionnaires using a Likert scale, while data analysis was conducted using multiple linear regression analysis with the assistance of SPSS software. The results indicate that the retail mix and service quality simultaneously have a positive and significant effect on consumers’ purchase decisions. Partially, the retail mix has a positive and significant effect on purchase decisions, while service quality also has a positive and significant effect and is the most dominant variable. These findings suggest that integrated retail strategies and improved service quality play an important role in encouraging consumers’ purchase decisions.